2023
DOI: 10.3389/fpls.2023.1272363
|View full text |Cite
|
Sign up to set email alerts
|

Stressing the importance of plant specialized metabolites: omics-based approaches for discovering specialized metabolism in plant stress responses

Mengxi Wu,
Trent R. Northen,
Yezhang Ding

Abstract: Plants produce a diverse range of specialized metabolites that play pivotal roles in mediating environmental interactions and stress adaptation. These unique chemical compounds also hold significant agricultural, medicinal, and industrial values. Despite the expanding knowledge of their functions in plant stress interactions, understanding the intricate biosynthetic pathways of these natural products remains challenging due to gene and pathway redundancy, multifunctionality of proteins, and the activity of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…Metabolites represent the biochemical end products of gene activity reflecting the adaptability of organisms ( Wu et al., 2023 ). In this study, we observed a trend of increasing changes in the number of DEMs with prolonged Cd stress peaking at 72 h before decreasing thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites represent the biochemical end products of gene activity reflecting the adaptability of organisms ( Wu et al., 2023 ). In this study, we observed a trend of increasing changes in the number of DEMs with prolonged Cd stress peaking at 72 h before decreasing thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have made rapid progress in understanding the mechanisms of pigment biosynthesis, and this includes a focus on flavonoid biosynthesis. Transcriptome and proteome analyses have proven to be valuable tools in elucidating the color biosynthesis mechanisms of various plants, and these methods have been successfully applied in studying commercial plants ( Wu, Northen & Ding, 2023 ). The application of RNA-Seq (transcriptome analysis) and proteomics has been instrumental in uncovering the networks that influence flower color.…”
Section: Genetic Basis Of Flower Color and Fragrancementioning
confidence: 99%